Induction of c-Fos expression in specific areas of the fear circuitry in rat forebrain by anxiogenic drugs. - Singewald, N; Salchner, P; Sharp, T (2003)
BACKGROUND: The fact that induction of anxiety- and panic-related symptoms is a property common to a range of drugs suggests that common neural substrates underlie their behavioral effects. METHODS: We used Fos immunocytochemistry to test the effects of four anxiogenic drugs (FG-7142, yohimbine, m-chlorophenylpiperazine [mCPP], and caffeine) on anxiety-related circuitry in rat forebrain. RESULTS: All four drugs commonly increased Fos-like immunoreactivity in 7 of 41 brain areas investigated, namely, central nucleus of the amygdala, bed nucleus of the stria terminalis, lateral septum, paraventricular nucleus of the hypothalamus, lateral hypothalamus, infralimbic and prelimbic cortex. All drugs but one (mCPP) also increased Fos expression in the basolateral and medial amygdala, the dorsomedial hypothalamus, cingulate cortex, and parts of the motor cortex. CONCLUSIONS: The results suggest that the anxiogenic drugs selected activate a restricted set of forebrain areas. Most of these areas have previously been shown to be activated by environmentally evoked anxiety and to have anatomic connections with hindbrain regions that are activated by the same drugs and by environmentally evoked anxiety. Together, these data are consistent with the theory of an integrated forebrain and hindbrain neuronal system that is important for anxiety states evoked by both drug and environmental manipulations.